Anatomical glenohumeral internal rotation deficit and symmetric rotational strength in male and female young beach volleyball players. (August 2016) - Saccol, Michele Forgiarini; Almeida, Gabriel Peixoto Leão; de Souza, Vivian Lima
Abstract: Beach volleyball is a sport with a high demand of shoulder structures that may lead to adaptations in range of motion (ROM) and strength like in other overhead sports. Despite of these possible alterations, no study evaluated the shoulder adaptations in young beach volleyball athletes. The aim of this study was to compare the bilateral ROM and rotation strength in the shoulders of young beach volleyball players. Goniometric passive shoulder ROM of motion and isometric rotational strength were evaluated in 19 male and 14 female asymptomatic athletes. External and internal ROM, total rotation motion, glenohumeral internal rotation deficit (GIRD), external rotation and internal rotation strength, bilateral deficits and external rotation to internal rotation ratio were measured. The statistical analysis included paired Student's t -test and analysis of variance with repeated measures. Significantly lower dominant GIRD was found in both groups ( p < 0.05), but only 6 athletes presented pathological GIRD. For strength variables, no significant differences for external or internal rotation were evident. Young beach volleyball athletes present symmetric rotational strength and shoulder ROM rotational adaptations that can be considered as anatomical. These results indicate that young practitioners of beach volleyball are subject to moderate adaptations compared to those reported for other overhead sports.